Practical APT Group Hash Unit Profiling Framework Using TTPs - LEE, Sena; KIM, Chaeyoung; PARK, Hoorin (IEICE Transactions on Information and Systems, 2024)
With the rise of cyber threats, identifying APT groups becomes increasingly crucial for enterprise security experts. This paper introduces a comprehensive framework for profiling APT groups, focusing on Lazarus and APT29. It underscores the critical role of malware hash unit profiling in contemporary cyber security efforts, aiming to fortify organizational defenses against evolving APT threats.